HALAL BIOTECHNOLOGY ON FERMENTATION AND LIQUID FERTILIZER PREPARATION FROM KOMBUCHA WASTE OF TECABLOWE WASTE IN INCREASING EGGPLANT (Solanum molengena) GROWTH - Muhammad Faizal Fathurrohim; Fajar Hidayanto; Firman Rezaldi; Yuliana Kolo; Kusumiyati (Universitas Mathla’ul Anwar Banten, 2022)
The fermented waste of butterfly pea flower kombucha can be used in the formulation and preparation of organic liquid fertilizer to support the growth of this eggplant plant. The purpose of this study was to determine the effectiveness of liquid fertilizer made from the waste of butterfly pea flower kombucha fermentation in supporting the growth of eggplant plants. The design of this study was a completely randomized design (CRD) with a single factor, namely the difference in the concentration of organic liquid fertilizer that had been treated five times. The data from this study were analyzed through ANOVA and DMRT. The results of this study have shown that the T5 treatment in the form of formulations and preparations of organic liquid fertilizer from a 5 mL/L concentration of Tela kombucha fermentation waste is the best treatment for the growth parameters of eggplant plant height, eggplant leaf number, and eggplant wet and dry weight, so that it can It was concluded that the butterfly pea flower kombucha can be used as a halal probiotic drink, and its waste can also be used as a halal organic liquid fertilizer to support the growth of eggplant plants.